Experience psychology - King, Laura A. (New York, 2010)
Experience Psychology is about, well, experience our own behaviors; our relationships at home and in our communities, in school and at work. Some of the content will be familiar to you, though much of it, especially the underlying science, may not be so familiar and may even come as a surprise. In keeping with the experiential theme, Experience Psy-chology is also a complete learning system designed to provide you with a personally meaningful, hands-on path to success in this course. An online diagnostic tool auto-matically adapts to your level of understanding-what you know and what you may not know-guiding you to specific activities, exercises, or readings that will improve understanding and likely your grade in the course. The book you hold in your hands (or are viewing on-screen), Experience Psychology, is designed to immerse you in a fascinating area of study and to guide you in connecting the science of psychology with your life.
Keywords: Psychology